2011
DOI: 10.1038/ismej.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the fecal microbial community in herbivorous land and marine iguanas of the Galápagos Islands using 16S rRNA-based pyrosequencing

Abstract: Herbivorous reptiles depend on complex gut microbial communities to effectively degrade dietary polysaccharides. The composition of these fermentative communities may vary based on dietary differences. To explore the role of diet in shaping gut microbial communities, we evaluated the fecal samples from two related host species-the algae-consuming marine iguana (Amblyrhynchus cristatus) and land iguanas (LI) (genus Conolophus) that consume terrestrial vegetation. Marine and LI fecal samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
172
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(196 citation statements)
references
References 29 publications
19
172
5
Order By: Relevance
“…Further, the presence of sulfate-reducing bacteria enhances the fermentation performance of some cellulolytic bacteria in vitro (Morvan et al, 1996b). Interestingly, sulfatereducing bacteria are present in the guts of herbivorous marine iguanas (Amblyrhynchus cristatus), and are thought to explain the lack of methanogenic archaea in these animals (Hong et al, 2011). We did not investigate the presence of methanogenic archaea in our experiment.…”
Section: Discussionmentioning
confidence: 95%
“…Further, the presence of sulfate-reducing bacteria enhances the fermentation performance of some cellulolytic bacteria in vitro (Morvan et al, 1996b). Interestingly, sulfatereducing bacteria are present in the guts of herbivorous marine iguanas (Amblyrhynchus cristatus), and are thought to explain the lack of methanogenic archaea in these animals (Hong et al, 2011). We did not investigate the presence of methanogenic archaea in our experiment.…”
Section: Discussionmentioning
confidence: 95%
“…The existence of active methanogens in the gut of herbivorous lizards has been detected by methane production from fecal material of captive iguanas (Hackstein and Van Alen, 1996). Recently, Hong et al (2011) reported an investigation of hindgut microbiota in three herbivorous reptiles from the Galapagos Islands: marine iguana (Amblyrhynchus cristatus), land iguana (Conolophus sp.) and giant tortoise (Geochelone nigra).…”
Section: Reptilesmentioning
confidence: 99%
“…Whereas marine iguanas feed primarily on soft macrophytic algae growing in intertidal and subtidal zones (Shepherd and Hawkes, 2005), land iguanas and giant tortoises feed on similar species of terrestrial vegetation (Christian et al, 1984). Intriguingly, Hong et al (2011) were unable to recover archaeal sequences from marine iguanas, perhaps because of very low methanogen densities. However, archaeal sequences were successfully amplified from the feces of the other hosts sampled.…”
Section: Reptilesmentioning
confidence: 99%
“…For many years, researchers have been trying to estimate the microbial diversity of complex environments, such as soil (9), marine systems (10), and animal gut systems (11,12). Various techniques have been developed, from culture-dependent methods to 16S rRNA genes-based methods of clone library (13,14), denaturing gradient gel electrophoresis (DGGE) (15), terminal restriction fragment length polymorphism (T-RFLP) (16), and the recently developed next-generation sequencing (17).…”
mentioning
confidence: 99%